Blood Markers in Healthy-Aged Nonagenarians: A Combination of High Telomere Length and Low Amyloidβ Are Strongly Associated With Healthy Aging in the Oldest Old - Fernández-Eulate, Gorka; Alberro, Ainhoa; Muñoz-Culla, Maider; Zulaica, Miren; Zufiría, Mónica; Barandiarán, Myriam; Etxeberria, Igone; Yanguas, José Javier; Gallardo, Maria Mercedes; Soberón, Nora; Lacosta, Ana María; Pérez-Grijalba, Virginia; et al. (Frontiers in Aging Neuroscience, 2018)
Many factors may converge in healthy ageing in the oldest old, but their association and predictive power on healthy o functionally impaired ageing has yet to be demonstrated. By detecting healthy ageing and in turn, poor ageing, we could take action to prevent chronic diseases associated with age. We conducted a pilot study comparing results of a set of markers (peripheral blood mononuclear cell telomere length or PBMC, circulating Aβ peptides, anti-Aβ antibodies, and ApoE status) previously associated with poor ageing or cognitive deterioration, and their combinations, in a cohort of “neurologically healthy” (both motor and cognitive) nonagenarians (n=20) and functionally impaired, institutionalized nonagenarians (n=38) recruited between 2014 and 2015. We recruited 58 nonagenarians (41 women, 70.7%; mean age: 92.37 years in the neurologically healthy group vs 94.13 years in the functionally impaired group). Healthy nonagenarians had significantly higher mean PBMC telomere lengths (mean=7, p=0.001), this being inversely correlated with functional impairment, and lower circulating Aβ40 (total in plasma fraction or TP and free in plasma fraction or FP), Aβ42 (TP and FP) and Aβ17 (FP) levels (FP40 131.35, p=0.004; TP40 299.10, p=0.007; FP42 6.29, p=0.009; TP42 22.53, p=0.019; FP17 1.32 p=0.001; TP17 4.47, p=0.3), after adjusting by age. Although healthy nonagenarians had higher anti-Aβ40 antibodies levels (net adsorbed signal or NAS +/- SD: 0.211 +/- 0.107), the number of participants that pass the threshold (NAS>3) to be considered as positive did not show such a strong association. There was no association with ApoE status. Additionally, we propose a “Composite Neurologically Healthy Ageing Score” combining TP40 and mean telomere length, the strongest correlation of measured biomarkers with neurologically healthy status in nonagenarians (AUC=0.904).